The Influence of Organization Culture, Work Environment and Leadership On Performance of Fulltime Lecturer (Case Study of Private Higher Education Institution which Supported by Corporate) - Hendy Tannady; Indira Santi Kerta Budi (Journal on Education, 2023)
The goals of this study were to examine and evaluate how leadership, organizational culture, and the workplace affect performance, both partially and collectively. The quantitative study methodology utilized involved distributing questionnaires to a population of permanent lecturers who work in private universities established by corporations. The sample contains 225 respondents. The study's conclusions show that corporate culture has a considerable, positive impact on performance, with an influence of 33.1% and a t-count of 13.334, based on multiple linear regression analysis performed using SPSS version 26. The second set of findings only partially supports the notion that the workplace positively and significantly affects performance, with an effect of 20.4% and a t-count of 3.529. The third set of results partially reveals that performance is positively and significantly impacted by leadership, with an influence of 10.7% and a t-count of 2.095.